The evolution of ber- verbs in Indonesian and English: A morphological and translation analysis - Neisya Neisya; Fitria Aprilia; Hastari Mayrita (Universitas Syiah Kuala, 2025)
This study aims to investigate how Indonesian verbs prefixed with ber- are translated into English, focusing on their semantic and grammatical transformations as part of a broader evolution of verbs across the two languages. It revealed how ber- verbs, shaped by affixation in Indonesian, evolved into structurally different forms in English, reflecting each languages grammatical tendencies. Using a descriptive qualitative method, the research analyzed a bilingual corpus derived from the Indonesian fairy tale Burung Hantu dan Putri Rajawali and its English translation The Owl and the Eagles Daughter. The data were collected through purposive sampling, comprising all ber- prefixed verbs in the source text. These verbs were analyzed based on their morphological forms, syntactic roles, and semantic shifts in translation. The analysis shows that most ber- verbs, such as berpikir (thought), bertemu (met), and berjuang (struggled), were translated using various English verb forms, including past tense, gerunds, and progressive aspect. Some verbs, such as berterima kasih (grateful) and berhadapan (ventured out), demonstrated more distinctive shifts, indicating cultural or idiomatic adaptation. Reduplicated forms like berkomat-kamit (muttered) and berjam-jam (for many hours) emphasized repeated or prolonged action, while the verb bekerja illustrated phonological alteration of the prefix. These findings highlight the translators strategies in rendering ber-verbs not only semantically but also functionally accurate in English, revealing the complex relationship of morphology, syntax, and meaning in cross-linguistic verb evolution.